On the Phragmén–Lindelöf Indicator for Random Entire Functions - Filevych, P. V. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
We establish that, for the “majority” of entire functions of finite order, their generalized Phragmén–Lindelöf indicators are identically equal to constants.